2003
DOI: 10.1046/j.1365-2109.2003.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature tolerance of Nile tilapia,Oreochromis niloticus: effects of environmental and dietary factors

Abstract: This study was conducted (1) to evaluate the effects of photoperiod (fixed vs. decreasing light), fish size (136 vs. 220 mm), dissolved ions (hardness and salinity) and diet (menhaden oil vs. coconut oilbased) on the tolerance (survival) of Nile tilapia, Oreochromis niloticus, to low temperatures (decreased by approximately 0.5 8C per day) and (2) to evaluate the effect of dietary fatty acid composition on selected physiological characteristics of Nile tilapia exposed to decreasing temperatures. Size significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 56 publications
1
47
0
3
Order By: Relevance
“…This result suggests that the high levels of polyunsaturated fatty acids of the n-3 series, and higher n-3/n-6 ratio increases the cold tolerance for red drum. However, a similar study with Nile tilapia (Atwood et al, 2003) did not show significant differences for cold tolerance, in spite of the profile changes in the body fatty acids observed.…”
Section: Discussionmentioning
confidence: 93%
“…This result suggests that the high levels of polyunsaturated fatty acids of the n-3 series, and higher n-3/n-6 ratio increases the cold tolerance for red drum. However, a similar study with Nile tilapia (Atwood et al, 2003) did not show significant differences for cold tolerance, in spite of the profile changes in the body fatty acids observed.…”
Section: Discussionmentioning
confidence: 93%
“…One study looked at lysozyme values for fixed photoperiod (light/dark 12:12, 24:0, and 14:10) in rainbow trout and noticed that LD 24:0 increased lysozyme after 7 days and for LD 14:10 after 30 days [11]. Another study showed no change in lysozyme of N1ile tilapia to reduced light periods [12]. The photoperiod was initially set to 12 L:12 D. Fish were allowed to acclimate for 6 days.…”
Section: Lysozymementioning
confidence: 98%
“…Mortality rate is also an important trait, and it can have direct implications on farm productivity. The survival of tilapia is affected by a great variety of factors, such as age (Wagner et al, 2004), cultivation density and water quality (Yi & Lin, 2001), and temperature and diet (Atwood et al, 2003). Few experiments have been carried out to study the genetic control of survival in tilapia (Chiayvareesajja et al, 1999;Charo-Karisa et al, 2006;Rezk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%